Using Question-And-Answer Teaching Method to Improve Students’ Self-Confidence in Speaking - Alda Bastin; Baso Jabu; Muhalim Muhalim (State University of Makassar, 2025)
This study aims to determine the effectiveness of the question-and-answer teaching method in improving students’ self-confidence in speaking English. This research employed a quantitative approach with a pre-experimental one-group pre-test and post-test design. The sample consisted of 34 students from class X.E4 at SMAN 5 Jeneponto, selected through purposive sampling. The research instrument was a speaking confidence test assessed using five self-confidence indicators adapted from Brown (2004), namely eye contact, facial expression, voice volume, fluency, and willingness to speak. The data were analyzed using a Paired Sample T-Test and N- Gain Score. The t-test result showed a significance value of 0.000 (p < 0.05), indicating a statistically significant difference between the students’ pre-test and post- test scores. The average N-Gain score was 0.19, which falls into the low category. Nevertheless, there was a positive shift in students’ confidence levels—from “Not Confident” to “Moderately Confident.” This low gain may have been caused by the short duration of the treatment. The study concludes that the question-and-answer method is effective in enhancing students’ speaking confidence, especially by creating an interactive and supportive classroom environment. Keywords: Question-and-Answer Teaching Method, Speaking Self-Confidence.